Bifunctional SnO2 Colloid Offers No Annealing Effect Compact Layer and Mesoporous Scaffold for Efficient Perovskite Solar Cells. (23rd June 2021) - Xiong, Liangbin; Li, Jiashuai; Ye, Feihong; Wang, Haibing; Guo, Yaxiong; Ming, Xing; Chen, Qingyun; Zhang, Shaoan; Xie, Ruihao; Chen, Zhanxu; Lv, Yang; Hu, Guangqi; et al.
Abstract: SnO2 compact layer (c‐SnO2 ) frequently suffers from degradation in high temperature processes (HTP) such as crack, worse interfacial contact, and electrical properties, that is, annealing effect. To solve this problem, a kind of bifunctional SnO2 colloid is developed by using small molecular oxalate whose organic components can be removed clearly at a low temperature process (LTP). The c‐SnO2 and SnO2 mesoporous layer (m‐SnO2 ) derived from the fresh and aged sols with the same colloid show no annealing effect, decreasing oxygen vacancy, and adsorbing water on increasing annealing temperature. The champion devices of LTP and HTP SnO2 planar perovskite solar cells (PSCs) achieve, respectively, stabilized photoelectric conversion efficiencies (PCEs) of 20.74% and 20.70%. In contrast, the performance of champion devices of their mesoporous counterparts is significantly improved, showing nearly hysteresis free character with stabilized PCEs of 22.40% and 22.37%, respectively. The inclusion of m‐SnO2 plays a role of an energy bridge, improving electrons collection efficiency, which is supported by photoluminescence and transient photoluminescence characterizations. HTP SnO2 mesoporous PSCs can preserve 97.6% and 80% of their initial PCEs after aging for 25 weeks and 8‐h irradiated/16‐h dark cycle within 104 h. The high stability of HTP SnO2 PSCs may ascribe to low oxygen vacancy and adsorbed water of HTP SnO2 . Abstract : A bifunctional SnO2 colloid is developed using small molecular oxalate. The resultant SnO2 films show "no annealing effect", contributing to stabilized PCEs of 22.40% and 22.37% for high temperature process (HTP) SnO2 planar and mesoporous PSCs, respectively. The high stability of HTP SnO2 PSCs may ascribe to low oxygen vacancy and adsorbed water of HTP SnO2 .